1996
DOI: 10.2172/985105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal aging on fracture toughness and charpy-impact strength of stainless steel pipe welds.

Abstract: The degradation of fracture toughness, tensile, and Charpy-impact properties of Type 308 stainless steel (SS) pipe welds due to thermal aging has been characterized at room temperature and 290°C. Thermal aging of SS welds results in moderate decreases in Charpy-impact strength and fracture toughness. For the various welds in this study, upper-shelf energy decreased by 50-80 J/cm 2 . The decrease in fracture toughness J-R curve or J IC is relatively small. Thermal aging had little or no effect on the tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For thermal embrittlement of cast SSs the fracture toughness of CF-8M steel represents the worst-case scenario. 28,30 It thus might represent a bounding case also for the synergistic effects of irradiation and thermal aging.…”
Section: Comparison With Fracture Toughness Data In the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…For thermal embrittlement of cast SSs the fracture toughness of CF-8M steel represents the worst-case scenario. 28,30 It thus might represent a bounding case also for the synergistic effects of irradiation and thermal aging.…”
Section: Comparison With Fracture Toughness Data In the Literaturementioning
confidence: 99%
“…[28][29][30] strength, hardness, and Charpy-impact transition temperature, and it decreases the ductility, fracture toughness, and impact strength. The extent of mechanical-property degradation is essentially determined by the chemical composition of the steel, the casting process used to construct the component, the ferrite content and ferrite morphology of the steel, and the time and temperature of service for the component.…”
Section: Synergistic Effect Of Thermal and Neutron Irradiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The embrittlement behavior that has been observed in stainless steels led the researchers to the investigation of the influence of low-temperature thermal aging on stainless steels weld joints [50][51][52][53][54][55][56][57][58][59][60]. The results of the experimental investigations have shown that the low-temperature decomposition of the ferrite → (α + α ) reduces both corrosion resistance and mechanical properties of the corrosion resistant steels and their welds and weld metals.…”
Section: Introductionmentioning
confidence: 99%